Developing a catering services mobile application for local community / Masturina Azmi and Norziana Yahya - Azmi, Masturina; Yahya, Norziana (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The catering booking system's mobile app for Gua Musang Kelantan's local community makes catering booking easier for both community members and catering owners. It has a user friendly interface, owner options, and food menus. The system allows for catering bookings to be made at any time, and the catering owner can access the booking list at all times. The app is being developed using Android Studio and Firebase, following an Agile Model with a clear lifecycle phase. This will help streamline the booking process and reduce wait times for the community.